Spatial Analysis of Urban Squares - Cutini, Valerio (TeMA - Journal of Land Use, Mobility and Environment, 2014)
Urban squares, despite their apparently self-evident consistency, actually represent one of the most uncertain issues of present urban planning. Denied and neglected by modern architecture, then sought after in the last decades, squares are commonly recognized as fundamental identity making elements in urban settlements as well as in their respective communities. Since their revival in the late ‘900, the design of urban squares has been a challenging task for generations of planners and urban designers, since, despite any effort, most of the squares worked out can hardly succeed in competing with the historic ones. What appears to explain the failure of most attempts is the actual uncertainty in the definition of what an urban square really is, or should be: not a mere open space, nor only a pedestrian path, nor necessarily a wide or regular space, nor always a junction of streets. Perhaps all these things together, but also something more, what makes the matter to overcome the limits of a strictly physical vision to approach social and cultural meanings. The purpose of this research is therefore to investigate around the link between spatial aspects and social issues, so as to identify the spatial features that allow an urban square to actually play a social and cultural role. As a testing ground of such effort a wide set of Italian squares was assumed as a case studies series, in order to catch the spatial code of their success as relation and public representation places; and some configurational parameters will then be proposed for reproducing such capability, so as to actually support the planning and design of urban squares.